Immunomonitoring of Stage IV Relapsed Neuroblastoma Patients Undergoing Haploidentical Hematopoietic Stem Cell Transplantation and Subsequent GD2 (ch14.18/CHO) Antibody Treatment - Seitz, Christian Martin; Flaadt, Tim; Mezger, Markus; Lang, Anne-Marie; Michaelis, Sebastian; Katz, Marie; Syring, Desireé; Joechner, Alexander; Rabsteyn, Armin; Siebert, Nikolai; Troschke-Meurer, Sascha; Zumpe, Maxi; et al. (Frontiers in Immunology, 2021)
Haploidentical stem cell transplantation (haplo SCT) in Stage IV neuroblastoma relapsed patients has been proven efficacious, while immunotherapy utilizing the anti-GD2 antibody dinutuximab beta has become a standard treatment for neuroblastoma. The combinatorial therapy of haplo SCT and dinutuximab may potentiate the efficacy of the immunotherapy. To gain further understanding of the synergistic effects, functional immunomonitoring was assessed during the clinical trial CH14.18 1021 Antibody and IL2 After haplo SCT in Children with Relapsed Neuroblastoma (NCT02258815). Rapid immune reconstitution of the lymphoid compartment was confirmed, with clinically relevant dinutuximab serum levels found in all patients over the course of treatment. Only one patient developed human anti-chimeric antibodies (HACAs). In-patient monitoring revealed highly functional NK cell posttransplant capable of antibody-dependent cellular cytotoxicity (ADCC). Degranulation of NK cell subsets revealed a significant response increased by dinutuximab. This was irrespective of the KIR receptor–ligand constellation within the NK subsets, defined by the major KIR receptors CD158a, CD158b, and CD158e. Moreover, complement-dependent cytotoxicity (CDC) was shown to be an extremely potent effector-cell independent mechanism of tumor cell lysis, with a clear positive correlation to GD2 expression on the cancer cells as well as to the dinutuximab concentrations. The ex vivo testing of patient-derived effector cells and the sera collected during dinutuximab therapy demonstrated both high functionality of the newly established lymphoid immune compartment and provided confidence that the antibody dosing regimen was sufficient over the duration of the dinutuximab therapy (up to nine cycles in a 9-month period). During the course of the dinutuximab therapy, proinflammatory cytokines and markers (sIL2R, TNFa, IL6, and C reactive protein) were significantly elevated indicating a strong anti-GD2 immune response. No impact of FcGR polymorphism on event-free and overall survival was found. Collectively, this study has shown that in-patient functional immunomonitoring is feasible and valuable in contributing to the understanding of anti-cancer combinatorial treatments such as haplo SCT and antibody immunotherapy.